Review of key technology and its application of blockchain - Feng ZHANG; Boxuan SHI; Wenbao JIANG (网络与信息安全学报)
The rise of blockchain technology is a paradigm shift,which is similar to the rise of the Internet,and it has attracted wide attention.Blockchain has characteristics of decentralization,tamper-resistant,traceability and so on.The achievements of some papers about blockchain at home and abroad have been analysed in recent years,and the core technology principle of blockchain has been parsed.The application scenarios of blockchain were disscussed,such as financial services,credit management,tenure management,public network service and other fields.The existing problems in various application fields were pointed out.Some opinions on the development and application of blockchain were put forward,dedicated to blockchain and hoped to do contribution for the research about blockchain and its applications.